2019
DOI: 10.3389/fonc.2019.00780
|View full text |Cite
|
Sign up to set email alerts
|

Common Molecular Alterations in Canine Oligodendroglioma and Human Malignant Gliomas and Potential Novel Therapeutic Targets

Abstract: Spontaneous canine ( Canis lupus ) oligodendroglioma (ODG) holds tremendous potential as an immunocompetent large animal model of human malignant gliomas (MG). However, the feasibility of utilizing this model in pre-clinical studies depends on a thorough understanding of the similarities and differences of the molecular pathways associated with gliomas between the two species. We have previously shown that canine ODG has an immune landscape and expression pattern of commonly described on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 113 publications
(149 reference statements)
1
8
0
Order By: Relevance
“…Other genes like C1QB and C1QC which are involved in complement cascade, KIAA0101 (or PCALF) in cell proliferation, and PARP9 performing in DNA damage repair have been known in literature to be up-regulated in GBM and promote tumorigenesis in consistent with our results (34)(35)(36)(37) while no witness was found for NUP37 as an encoding gene for Nucleoporin 37; a member of nuclear pore complex (NPC) which also was shown to be upregulated in the signature. On the other side, CLDN10 encoding claudin 10 in Tight junction interactions and RAB11FIP4 located on chromosome 17q11.2 and encodes for Rab11 family-interacting protein 4 which plays role in the regulation of endocytic tra c, both were shown to be down-regulated in the signature in consistent with the past ndings (38)(39)(40), although a controversial result also has been reported for the latter (41).…”
Section: Discussionsupporting
confidence: 90%
“…Other genes like C1QB and C1QC which are involved in complement cascade, KIAA0101 (or PCALF) in cell proliferation, and PARP9 performing in DNA damage repair have been known in literature to be up-regulated in GBM and promote tumorigenesis in consistent with our results (34)(35)(36)(37) while no witness was found for NUP37 as an encoding gene for Nucleoporin 37; a member of nuclear pore complex (NPC) which also was shown to be upregulated in the signature. On the other side, CLDN10 encoding claudin 10 in Tight junction interactions and RAB11FIP4 located on chromosome 17q11.2 and encodes for Rab11 family-interacting protein 4 which plays role in the regulation of endocytic tra c, both were shown to be down-regulated in the signature in consistent with the past ndings (38)(39)(40), although a controversial result also has been reported for the latter (41).…”
Section: Discussionsupporting
confidence: 90%
“…27 It has been shown that canine oligodendrogliomas are more genetically similar to human glioblastomas than human oligodendrogliomas, particularly in terms of upregulated genes. 28 Favorable IDH1 mutations and 1p/19q codeletions are rare in canine tumors. 28 Due to differences in arrangement of the dog and human genome, it may be that canine oligodendrogliomas possess sufficient genetic information to behave as aggressively as WHO grade IV glioblastomas in humans, as evidenced by similar patterns of resistance to antitumoral agents and systemic immune interference.…”
Section: Figmentioning
confidence: 99%
“…28 Favorable IDH1 mutations and 1p/19q codeletions are rare in canine tumors. 28 Due to differences in arrangement of the dog and human genome, it may be that canine oligodendrogliomas possess sufficient genetic information to behave as aggressively as WHO grade IV glioblastomas in humans, as evidenced by similar patterns of resistance to antitumoral agents and systemic immune interference. 29 Overall, survival in our cohort has been favorable and is clearly superior to that in published data on outcomes in palliated dogs with gliomas.…”
Section: Figmentioning
confidence: 99%
“…Gliomas are a group of devastating brain tumors that affect both dogs and humans. 1,3,11,50,64,69,72 They represent approximately 35% of primary intracranial tumors in the dog and are overrepresented in brachycephalic breeds such as the boxer, Boston terrier, and English and French bulldog. 49,64,73 Glioma subtypes in humans include oligodendroglioma, astrocytoma, and glioblastoma, and in dogs are oligodendroglioma, astrocytoma, and undefined glioma.…”
mentioning
confidence: 99%